Nigerian law of landlord and tenant - Onwuamaegbu, M. Obumneme (London : Sweet & Maxwell; Lagos : African Universities P., 1966)
The book attempts to restate the main principles of the applicable laws, and at the same time to make a jurisprudential comparison of the institutions, concepts, rules and techniques of the different bodies of law, with a view to their explanation and harmonization.
Includes bibliographical references and index.
rpm 24/01/2019
Loans
Keywords: Landlord and tenant